High Frequency of Clinically Significant Bacteremia in Adults Hospitalized With Falciparum Malaria. (9th February 2016) - Nyein, Phyo Pyae; Aung, Ne Myo; Kyi, Tint Tint; Htet, Zaw Win; Anstey, Nicholas M.; Kyi, Mar Mar; Hanson, Josh
Abstract : Background. African children with severe falciparum malaria commonly have concomitant gram-negative bacteremia, but co-infection has been thought to be relatively rare in adult malaria. Abstract: Background.  African children with severe falciparum malaria commonly have concomitant Gram-negative bacteremia, but co-infection has been thought to be relatively rare in adult malaria. Methods.  Adults with a diagnosis of falciparum malaria hospitalized at 4 tertiary referral hospitals in Myanmar had blood cultures collected at admission. The frequency of concomitant bacteremia and the clinical characteristics of the patients, with and without bacteremia, were explored. Results.  Of 67 adults hospitalized with falciparum malaria, 9 (13% [95% confidence interval, 5.3%–21.6%]) were also bacteremic on admission, 7 (78%) with Gram-negative enteric organisms ( Escherichia coli [n = 3], typhoidal Salmonella species [n = 3], nontyphoidal Salmonella [n = 1]). Bacteremic adults had more severe disease (median Respiratory Coma Acidosis Malaria [RCAM] score 3; interquartile range [IQR], 1–4) than those without bacteremia (median RCAM score 1; IQR, 1–2) and had a higher frequency of acute kidney injury (50% vs 16%, P = .03). Although 35 (52%) were at high risk of death (RCAM score ≥2), all 67 patients in the study survived, 51 (76%) of whom received empirical antibiotics on admission. Conclusions.  Bacteremia was relatively frequent in adults hospitalized with falciparum malaria in Myanmar. Like children in high transmission settings, bacteremic adults in this low transmission setting were sicker than nonbacteremic adults, and were often difficult to identify at presentation. Empirical antibiotics may also be appropriate in adults hospitalized with falciparum malaria in low transmission settings, until bacterial infection is excluded.